2012
DOI: 10.1021/ja2095766
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Core Flexibility Modulates Enzyme Activity in HIV-1 Protease

Abstract: Human immunodeficiency virus Type-1 (HIV-1) protease is crucial for viral maturation and infectivity. Studies of protease dynamics suggest that the rearrangement of the hydrophobic core is essential for enzyme activity. Many mutations in the hydrophobic core are also associated with drug resistance and may modulate the core flexibility. To test the role of flexibility in protease activity, pairs of cysteines were introduced at the interfaces of flexible regions remote from the active site. Disulfide bond forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 30 publications
5
83
0
Order By: Relevance
“…HIV-1 protease is a highly dynamic protein, and conformational dynamics, especially around the active site, is crucial to substrate binding and enzymatic activity (32)(33)(34)(35)(36). Although crystal structures provide key insights, alteration of dynamic behavior, not captured by static structures, is emerging as an additional contribution to mechanisms of drug resistance (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 protease is a highly dynamic protein, and conformational dynamics, especially around the active site, is crucial to substrate binding and enzymatic activity (32)(33)(34)(35)(36). Although crystal structures provide key insights, alteration of dynamic behavior, not captured by static structures, is emerging as an additional contribution to mechanisms of drug resistance (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Slow exchange is expected here due to low solvent accessibility and a complex network of interactions around the active-site core. The flap tips (residues at positions [49][50][51][52][53] are the regions of the proteases that display the fastest deuterium incorporation. The flaps are completely solvent-exposed and highly mobile.…”
Section: Dynamics Of the Hiv-1 Proteasesmentioning
confidence: 99%
“…Polymorphic sites of the subtype B protease (PDB ID: 2PC0) [13] and the C-SA protease (PDB ID: 3U71) [37]. The flexible flaps of the protease (residues at positions [46][47][48][49][50][51][52][53][54] are coloured cyan. The fulcrum region (residues at positions 10-23), hinge region (residues at positions 35-42 and 57-61) and cantilever region (residues at positions 62-78) are implicated in flap opening.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of protease inhibitor (PI) resistance mutations in HIV-1 PR suggested that some PR mutations contribute to the flexibility of the hydrophobic core of the enzyme, a mechanism that has been called hydrophobic sliding (33,34). In this mechanism, some of the resistance mutations that reduce the susceptibility of PR to PIs allow some of the hydrophobic core residues in PR to exchange interactions, allowing the residues (and the enzyme) more conformational flexibility, which in turn affects the processing of the cleavage sites in the HIV-1 polyproteins and reduces the binding of PIs that prevent these essential cleavages (33,34).…”
Section: Discussionmentioning
confidence: 99%